Case report: Successful extracorporeal cardiopulmonary resuscitation despite severe metabolic acidosis after refractory out-of-hospital cardiac arrest - Kavaliukaite, Loreta; Diaconescu, Anca-Isabela; Eis, Doris; Slankamenac, Ksenija (Frontiers in Disaster and Emergency Medicine, 2024)
Current guidelines suggest considering extracorporeal cardiopulmonary resuscitation (ECPR) in refractory cardiac arrest and provide some guidance for favorable prognostic factors. However, inclusion and exclusion criteria are not strictly defined. We describe a 60-year-old male who underwent extracorporeal life support (ECLS) following refractory out-of-hospital cardiac arrest and made a full neurological recovery despite severe metabolic derangements, including a pH of 6.6 and lactate of 29 mmol/l. The aim is to present a favorable neurological outcome after ECPR despite severe significant physiologic derangements and put relative contraindications for ECPR into perspective.